PENGEMBANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB SEBAGAI SISTEM PENGOLAHAN NILAI SISWA DI SMK NEGERI 1 KUDUS - Farid Suryandani; Basori Basori; Dwi Maryono (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
This research aims to produce an information system of grade processing to allow the teacher in manage a report card of student grade. This information system is intended for use in vocational high school. This information system is web based, so it can be accessed by teacher to manage grades and students can see the result of their study. Method of this research is research and development (R&D) that implemented in SMK Negeri 1 Kudus. The data collection techniques are interview, quesioner and documentation. The Development of Academic Information System as a Web Based on Processing System of Student Grade in SMK Negeri 1 Kudus carried out with five stages : (1) Communication is discussions between researchers with the school about developing the system, (2) Planning is the planning needs of the functional, software and hardware requirements of the system are developed, (3) Modeling is the stage of system design that focuses on data processing. This phrase begins with the making of Usecase Diagram, Flowchart, DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), Design of data base tables and their relationships and manufacturing design of interface system, (4) Construction is the stage where the design has been created, implemeted into the code (programme), (5) Deployment is the testing phrase to SMK to get feedback on the feasibility and development of a system which further. The final value of this research is 93,1% from expert system, 85,3% from the teacher and administration staff and 82.,4 % from the students, so it means that the system is highly feasible to be used.